Addressing moral hazard and premium rate heterogeneity in crop insurance: applications in pesticides and hurricanes - Biram, Hunter (Kansas State University, 2022)
Essay 1: Crop Insurance Participation has Heterogeneous Impacts on Pesticide Use Two major goals of agricultural policy include smoothing farm income fluctuations through risk management programs and reducing the environmental impact of chemical inputs. An unforeseen outcome in achieving these goals is the potential for moral hazard in which producers alter applications of chemicals, such as pesticides, upon obtaining federally subsidized crop insurance. This raises the question of whether crop insurance participation effects pesticide use and if the effect is heterogeneous across crops. In this work, we utilize state-level panel data for 45 states in the U.S. over the span of 1965-2019 within a shift-share instrumental variables framework and find that participating in crop insurance results in heterogeneous treatment effects on pesticide use across six major crops. For corn, soybeans, and sorghum, the treatment effect is negative and robust to measurement and model specification, while wheat, cotton, and rice give more nuanced estimated treatment effects across measurement of the pesticide use decision. Previous studies give mixed findings for the estimated treatment effect, which can likely be attributed to various estimation approaches, measurements of key policy variables, and differences in management practices across crops. Therefore, measuring the effect of crop insurance participation on pesticide use should be done with caution, and policies formed from empirical findings should consider the many nuances uncovered here before enacting them into public law.   Essay 2: Hurricane Incidence Results in Significant Increases to Crop Damages: Evidence from the Mississippi Delta Every year crop producers cope with many risks. While exposure to some risks is more universal, such as price volatility and global trade policies, exposure to others may be felt differently across regions, like extreme weather such as hurricanes. An increased risk of hurricanes presents a potential threat to agricultural production systems in areas prone to this risk leading crop producers to adopt various risk management tools such as crop insurance which requires a producer to pay a subsidized premium. This work aims to measure the impact of hurricane incidence on damages for crops grown in the Mississippi Delta (i.e., Arkansas, Louisiana, and Mississippi). We leverage county-level panel data spanning 2002-2021 from the USDA-RMA Summary of Business and Cause of Loss, and daily data from the NOAA National Hurricane Center using a novel measure for hurricane treatment assignment under a Difference-in-Differences identification strategy and find that hurricanes result in increases in on-farm damages for yield and revenue insurance products across all crops predominantly grown in the region. We find on-farm damages conditional on a hurricane happening to result in up to a 20-percentage point increase in loss-cost ratios (LCR) for yield and revenue insurances across all crops considered. Our findings align with previous studies which find decreases in mean yields and increases in yield variability caused by more frequent catastrophic weather events resulting in a fall in producer welfare. With an ever-changing climate, measuring the impact of hurricanes and other extreme weather events, on agricultural production is of the utmost importance.
Keywords: Crop insurance; Moral hazard; Risk assessment; Causal inference; Agricultural economics; Applied econometrics